2015
DOI: 10.3389/fpsyg.2015.00927
|View full text |Cite
|
Sign up to set email alerts
|

Neural encoding of large-scale three-dimensional space—properties and constraints

Abstract: How the brain represents represent large-scale, navigable space has been the topic of intensive investigation for several decades, resulting in the discovery that neurons in a complex network of cortical and subcortical brain regions co-operatively encode distance, direction, place, movement etc. using a variety of different sensory inputs. However, such studies have mainly been conducted in simple laboratory settings in which animals explore small, two-dimensional (i.e., flat) arenas. The real world, by contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 43 publications
(59 reference statements)
1
39
0
Order By: Relevance
“…As the bat flies, and the vector between the moving bat and its goal changes, different goal direction cells become active or fall silent [Sarel et al, 2017]. Rats spatial neurons, in contrast, appear to reduce the problem of navigating in 3D space to navigation in a 2D plane, even when that plane is inclined, vertical, or inverted [Jeffrey et al, 2015]. Rat spatial neurons treat the plane of locomotion as the space in which orientation occurs, sometimes with loss of resolution if the plane of locomotion departs from the horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…As the bat flies, and the vector between the moving bat and its goal changes, different goal direction cells become active or fall silent [Sarel et al, 2017]. Rats spatial neurons, in contrast, appear to reduce the problem of navigating in 3D space to navigation in a 2D plane, even when that plane is inclined, vertical, or inverted [Jeffrey et al, 2015]. Rat spatial neurons treat the plane of locomotion as the space in which orientation occurs, sometimes with loss of resolution if the plane of locomotion departs from the horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…The only other bat claustrum report focused on the interconnections of auditory cortex and showed connectivity of the latter with frontal, anterior cingulate, retrosplenial and perirhinal cortices, the claustrum, and subcortical targets including the amygdala, auditory thalamus, pons, pretectum, superior and inferior colliculi, and central gray (Fitzpatrick et al, ). As described in the introduction, place, head‐direction, and grid cell recordings during navigational behavior have shown that individual place cells in bats are active in confined 3D volumes and nearly all neurons encode all three axes with similar resolution (Yartsev and Ulanovsky, ), whereas cells in rodents are multiplanar, but not fully volumetric (Stackman et al, ; Hayman et al, , ; Taube and Shinder, ; Taube et al, ; Jeffery et al, ). We speculate that a major basis for the multiplanar cell streams of the bat claustrum compared with rodent is the need for bats to function in three dimensions, and make decisions based on multisensory input in flight at higher speed with little margin for error (see e.g., Bar et al, ; Marshall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bats have been shown to differ from rodents in the activity of specific brain regions and circuits. Studies of place, head‐direction, and grid cells in navigational behavior have shown clear coding of three dimensions in bats (Yartsev and Ulanovsky, ), but only variations of two‐dimensional coding in rodents (Stackman et al, ; Hayman et al, , ; Taube and Shinder, ; Taube et al, ; Jeffery et al, ). These findings demonstrate functional differences between theses species and reinforce the idea that the two‐dimensional existence of rodents and the three‐dimensional existence of bats are different.…”
mentioning
confidence: 99%
“…Place cells are neurons in the hippocampus that fire when an animal visits specific regions of its environment, called place fields, and are thought to provide the foundation for an internal representation of space, or ‘cognitive map’ 1, 2 . The question arises as to whether this map is three-dimensional, and if so whether its properties are the same in all dimensions, and how information is integrated across these dimensions 35 . This is important not just for spatial mapping per se but also because the spatial map may form the framework for other types of cognition in which information dimensionality is higher than in real space.…”
Section: Introductionmentioning
confidence: 99%